A waffle structured composite for RCS reduction via absorption and scattering mechanisms. (February 2023) - Jiang, Qian; Duan, Jinming; Uddin, Azim; Wu, Xianyan; Yi, Honglei; Wu, Liwei
Graphical abstract: Highlights: The unique waffle structure realized the collaborative mechanisms of absorption and scattering towards electromagnetic waves. The RCS reduction below −10 dB was achieved for WSC, and the peak reached to −30 dB. The dielectric loss is the main cause of absorption for waffle structured composite. The waffle structure formed by one-step knitting process facilitates the continuous large-scale manufacture. Abstract: A radar absorbing material named waffle structured composite (WSC) was proposed based on the periodic structure element formed by one-step double-sided knitting process with the advantage of continuous manufacture. The unique waffle structured pattern shaped by the knitted loops achieved the integration of structure and function. By realizing the collaborative mechanisms of absorption and scattering, the radar cross section (RCS) below −10 dB was achieved in the range of 6–8 GHz and 12–18 GHz towards the wale and course directions, respectively, and RCS reduction peak reaches to −30 dB. Through the S-parameter analysis and electromagnetic simulation, it can be revealed that the low-frequency RCS reduction in the wale direction was mainly dominated by the absorption mechanism, and the high-frequency RCS reduction in the course direction was led by the scattering mechanism. Furthermore, to further explore the scattering and absorption mechanism, phase difference, dielectric loss and magnetic loss were investigated in details. It was verified that the absorption of WSC is mainly originated from dielectric loss with slight magnetic loss, and Debye relaxation plays the important role in dielectric loss. The WSC proposed in this paper is equipped with characteristics of good RCS reduction and continuous large-scale manufacture, which is promising in practical engineering application of radar stealth.